Impact of Mungbean Yellow Mosaic Virus Disease on Seed Planting Value of Soybean - KUNIKA SILODIA; USHA BHALE; MS BHALE (Seed Research, 2026)
An epidemic of Mungbean Yellow Mosaic Virus (MYMV) disease was recorded in soybean at V3- R2 stage under agro-conditions of Jabalpur (MP), that favored by temperature (26.5 to 27° C) and relative humidity (75-80%), with presence of population of whiteflies up to 25 flies/leaf (trifoliate), higher rainfall (116.80 mm) with more number of rainy days (four). Within a period of 10-12 days the entire soybean plant population was infected by vector borne pathogen (Bemisia tabaci) in the region. Loss in seed germination (35.58%), seed emergence (44.41%), seed weight (37.2%) and seed vigor (55.27%) was noticed in JS 335 obtained from no- disease and more than 60% infected plant population. A slight change in seed morphology was observed in seeds from diseased plants. The seed from infected plants has elliptical shape as compared to normal oval shape. No seed coat cracking was observed. The viability test of soybean seeds obtained from healthy and infected plants indicated no difference. The infection of MYMV did not attack the embryo, as evident in standard tetrazolium test.